The Relationship between population fluctuations of Helopeltis theivora Waterhouse, availability of Cocoa Pods and Rainfall Pattern - Muhamad Awang, Rita; Chung, Gait Fee (Universiti Putra Malaysia Press, 1993)
Investigation on factors affecting the population fluctuations of Helopeltis theivora in relation to food supply and rainfall in the field was conducted. Results showed that population fluctuations seem to be dictated by rainfall and numbers of available pods as shown by positive correlations between them. The results also showed a significant yield decrease with increased mind populations. The numbers of cherelles and pods on a tree determine it attractiveness, since significantly more cherelles and pods were found on infested trees than on uninfested trees.